Ultrasonic sensor for imaging measurement techniques - Mansor, Mohammad Amaluddin; Goh, Chiew Loon; Abdul Rahim, Ruzairi; Puspanathan, Jaysuman; Nor Ayob, Nor Muzakkir (Penerbit UTHM, 2016)
Generally, are many methods for imaging measurement techniques, traditional and modern method and still have pros and cons between these two ways. Basically, the traditional techniques method is reported does not fully meet the specification of modern industry nowadays. Traditional method mainly includes electromagnetic detection, eddy current testing and etc. Differ with the modern method which is using the ultrasonic for imaging techniques and involving the laser ultrasonic, ultrasonic velocity, real time ultrasonic and off axis propagation of ultrasonic which be define the modern method is widely used industry to improve from the traditional method. Rumoured has been widely separate that modern techniques of imaging measurement are gaining popularity from every industry such as in medical instrument, construction instrument, synthetic aperture and holographic imaging measurement. Modern industry has proposed various method in using the ultrasonic in order to improve the quality of work in industry. Several advantages have been discovered while using the ultrasonic industry such as in mediation which is ultrasonic is used to improve the imaging in human soft tissue, meanwhile in construction ultrasonic giving an advantage in defect detection in specific information such as the location on defection and the size of defection. Besides that, in real time ultrasonic imaging is giving an advantage in focusing for multi-layered objects with synthetic aperture and lastly ultrasonic also give an advantage in guided wave in thin orthotropic layers which is its been use for dynamic holographic imaging measurement.